B-Via Spa & Beauty Center / Mohd Faizal Md Tawil ... [et al.] - Md Tawil, Mohd Faizal; Zakaria @ Ali, Ishak; Yaakob, Islaili Ulfaii; Fautzie, Nor Asyafa; Ali, Juliana (Faculty of Applied Sciences, 2006)
First of all, our company named as B-ViA SPA & BEAUTY CENTER in form of partnership. Our company main activities are provide services such as body treatment, sauna, traditional massage, nail treatment, and aromatic bath. Our target market is student, workers, people around Shah Alam and also single person. The operation building is located at Lot 4-F-04 & 4- F-08,4st Floor, SACC Mall, Jalan Perbadanan 14/9,Seksyen 14,40000 Shah Alam, Selangor. It's located inside The Shah Alam City Center or famous names as SACC Mall. It's very strategic area because there are famous shopping complex that can attract peoples to come.